Actively Involving Middle School Students in the Implementation of a Pilot of a Behavioral Economics–Based Lunchroom Intervention in Rural Schools. Issue 5 (September 2019) - Askelson, Natoshia M.; Brady, Patrick; Ryan, Grace; Meier, Cristian; Ortiz, Cristina; Scheidel, Carrie; Delger, Patti
School-based interventions can play an important role in improving childhood and adolescent nutrition and preventing obesity. Schools offer a unique opportunity to implement policy, systems, and environmental interventions targeting healthy eating behaviors. An intervention was piloted in six middle schools featuring behavioral economics–based changes to the lunchroom, communication training, and communicate cues for food service staff. The pilot study employed a multicomponent evaluation with students and food service directors and staff including a lunchroom assessment, online surveys, production records, and interviews. Five schools increased their scores on the lunchroom assessment tool, and four schools increased the number of servings produced of healthy food items. Interviews with food service directors indicated the interventions was feasible and well received. School-based policy, systems, and environmental interventions targeting healthy eating behaviors may play a role in preventing obesity in children and adolescents.